2007
DOI: 10.1523/jneurosci.0164-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Synaptic Morphology Accompany Actin Signaling during LTP

Abstract: Stabilization of long-term potentiation (LTP) is commonly proposed to involve changes in synaptic morphology and reorganization of the spine cytoskeleton. Here we tested whether, as predicted from this hypothesis, induction of LTP by theta-burst stimulation activates an actin regulatory pathway and alters synapse morphology within the same dendritic spines. TBS increased severalfold the numbers of spines containing phosphorylated (p) p21-activated kinase (PAK) or its downstream target cofilin; the latter regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
306
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 266 publications
(335 citation statements)
references
References 60 publications
27
306
2
Order By: Relevance
“…[28][29][30] We used wide-field imaging followed by 3-dimensional deconvolution tomography, a method enabling analysis of hundreds of thousands of synapses. 43,44 We sampled systematically dorsal (septal) and ventral (temporal) hippocampus, and compared the effects of restraint and multimodal stresses (Figures 2a and d). PSD-95 localized to the heads of GFP-expressing dendritic spines of hippocampal pyramidal neurons, (Figure 2c), so that counts of PSD-95 puncta provided a measure of dendritic spines and synapses.…”
Section: Resultsmentioning
confidence: 99%
“…[28][29][30] We used wide-field imaging followed by 3-dimensional deconvolution tomography, a method enabling analysis of hundreds of thousands of synapses. 43,44 We sampled systematically dorsal (septal) and ventral (temporal) hippocampus, and compared the effects of restraint and multimodal stresses (Figures 2a and d). PSD-95 localized to the heads of GFP-expressing dendritic spines of hippocampal pyramidal neurons, (Figure 2c), so that counts of PSD-95 puncta provided a measure of dendritic spines and synapses.…”
Section: Resultsmentioning
confidence: 99%
“…We tested this by counting synapses associated with a high concentration of pCofilin. This constitutively active protein severs developing actin filaments unless inactivated by phosphorylation, a step that is critical to the production of the cytoskeletal changes required for LTP consolidation (Chen et al 2007;Rex et al 2009). Previous studies showed that unsupervised learning in a simple open field by rats with no prior experience increases the percentage of hippocampal synapses containing relatively high levels of pCofilin within hippocampal field CA1; an NMDA receptor antagonist blocked both the synaptic changes and memory encoding (Fedulov et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…For both analyses, rats were then immediately euthanized by decapitation under isoflurane inhalation anesthesia. Brains were fast frozen and cryostat sectioned; slide mounted sections were fixed in methanol and processed for dual immunofluorescence as described (Chen et al 2007) using mouse anti-PSD-95 (1:1000; ThermoFisher Scientific #MA1-045) and rabbit pCofilin Ser3 (1:1000 Abcam #12866) and secondary antisera including AlexaFluor488 anti-mouse IgG and AlexaFluor594 anti-rabbit IgG (both 1:1000, Invitrogen). Some sections were processed without one or the other primary antisera to verify an absence of secondary antisera cross-reactivity or channel bleed-through.…”
Section: Analyses Of Synapse Immunolabeling (See Supplemental Methods)mentioning
confidence: 99%
See 2 more Smart Citations